2019
DOI: 10.14716/ijtech.v10i1.2215
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Beauveria bassiana on the Effectiveness of Nicotiana tabacum Extract as Biopesticide Against Hypothenemus hampei to Robusta Coffee

Abstract: This study examined the effect of the addition of Beauvaria bassiana on the effectiveness of Nicotiana tabacum extract as a biopesticide against coffee berry borer (CBB) or Hypothenemus hampei. A six months field experiment was carried out to examine the combined biopesticide effect on robusta coffee plantation. Randomized complete block design (RCBD) was used as a model for this experiment that consists of two factors. The first factor was the composition of Beauveria bassiana in water (0 to 320 g), while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 5 publications
1
11
0
1
Order By: Relevance
“…e previous studies reported that N. tabacum extract had been used to eradicate and prevent most insects and other pests. e combination of 320 g Beauveria bassiana/ 8 L of water and 30 mL Nicotiana tabacum extract/10 L of water was found to be able to reduce the percentage and intensity of coffee fruit attacked by CBB to 1.54% and 0.33%, respectively [29]. e attack of cabbage looper (Trichoplusia binotalis), as the significant insects under field conditions in cabbage plantation, was also significantly lower with an application of 3% aqueous extract of N. tabacum.…”
Section: Introductionmentioning
confidence: 94%
“…e previous studies reported that N. tabacum extract had been used to eradicate and prevent most insects and other pests. e combination of 320 g Beauveria bassiana/ 8 L of water and 30 mL Nicotiana tabacum extract/10 L of water was found to be able to reduce the percentage and intensity of coffee fruit attacked by CBB to 1.54% and 0.33%, respectively [29]. e attack of cabbage looper (Trichoplusia binotalis), as the significant insects under field conditions in cabbage plantation, was also significantly lower with an application of 3% aqueous extract of N. tabacum.…”
Section: Introductionmentioning
confidence: 94%
“…Coffee is undoubtedly one of the most popular drinks around the world, and for this reason, it has been widely studied (Mahachandra et al, 2017;Iswanto et al, 2019;Haryuni et al, 2019). Its commercialization occupies a very important place in the economies of countries like Colombia, Brazil, and Vietnam, among others.…”
Section: Introductionmentioning
confidence: 99%
“…e use of plant-based pesticides provides a double advantage, i.e., producing safe products to humans as well as no pollution to the environment [6]. Previous studies on Nicotiana tabacum extracts produced by using solvent extraction as well as pyrolysis methods have shown a significant effect of those extracts on various fungus and insects [7][8][9][10][11][12]. e extract reduces the protein content of robusta skin, resulting in reduced attack by insects [11,12].…”
Section: Introductionmentioning
confidence: 99%